Metabolic diversity in sorghum: Mechanism underlying grain color variation and fermentation quality - Fan Yang; Jiaqi Qiao; Miao Yang; Dongye Liu; Huimei Sun; Xinxin Wang; Xiao Zhang; Dongao Huo (PLoS ONE, 2025)
Sorghum (Sorghum bicolor L. Moench) serves as a critical staple cereal, forage crop, and primary raw material for baijiu (Chinese distilled spirits) production and vinegar fermentation. In this study, we performed comprehensive untargeted metabolomic profiling on widely cultivated sorghum accessions exhibiting diverse grain color phenotypes, followed by in-depth characterization of their metabolic signatures. The results demonstrated significant inter-accession variability in metabolite composition, with GL18 showing the most pronounced accumulation of metabolites within the phenylpropanoids and polyketides class. KEGG pathway enrichment analysis revealed substantial divergence in flavonoid biosynthetic pathways among accessions, particularly in the biosynthesis of naringenin, delphinidin, cyanidin, and pelargonidin 3-glucoside—key pigments correlated with grain color variations. Metabolite profiling further identified distinct accumulation patterns of flavor precursors (e.g., β-phenylethanol precursors), amino acids (e.g., tryptophan, L-leucine), and glycosides (e.g., L-rhamnofuranose) that significantly influence baijiu sensory quality attributes. For vinegar fermentation, significant inter-accession differences were observed in carbohydrate (sucrose, mannitol), amino acid (L-proline, arginine), and organic acid (lactic acid, quinic acid) accumulation profiles, which correlated with fermentation efficiency and final product quality. This study provides novel insights into the metabolic basis of sorghum grain color diversity and highlights the potential for tailored sorghum accessions to enhance the quality and diversity of baijiu and vinegar products, thereby contributing to the optimization of crop quality and agricultural resource efficiency.